Does progesterone supplementation improve pregnancy rates in clomiphene citrate and intrauterine insemination treatment cycles?. (March 2015) - Elguero, Sonia; Wyman, Allison; Hurd, William W.; Barker, Nichole; Patel, Bansari; Liu, James H.
Abstract Aim: To investigate the effect of empiric use of luteal phase progesterone supplementation to improve endometrial receptivity in women undergoing treatment with clomiphene citrate in combination with intrauterine insemination (CC-IUI). Design: Retrospective cohort analysis. Setting: University fertility center. Patients: 426 CC-IUI cycles from 292 patients with unexplained infertility. Interventions: Patients were treated with micronized intravaginal progesterone 100 mg twice daily beginning approximately three days after CC-IUI. Main outcome measure(s): Clinical pregnancy per initiated cycle as defined by presence of fetal heart rate on ultrasound. Results: Clinical pregnancy rate was higher in patients receiving luteal phase support compared to patients not receiving luteal phase support (odds ratio: 2.04; 95% confidence interval: 1.01–4.14) after adjusting for all factors in the analysis using a multivariate logistic regression model. Age at the start of the cycle, BMI and CC dose were not shown to have an effect on clinical pregnancy rates. Patients with endometrial lining (EML) thickness 6–8 mm and >8 mm had increased clinical pregnancy rates compared to EML <6 mm independent of luteal phase progesterone use. Patients who appear to receive the greatest benefit of progesterone supplementation are in the 6–8 mm EML cohort. Conclusions: Luteal phase progesterone supplementation in CC-IUI cycles can improve endometrial receptivity as judged by the improved clinical pregnancy rates as the primary outcome.